Improving child nutrition and development through community-based child care centres (CBCCs) in Malawi - Twalibu, Aisha; Roschnik, Natalie; Gelli, Aulo; Katundu, Mangani; Chidalengwa, George; Phiri, Peter; Moestue, Helen (2018)
Community-based childcare centres (CBCCs) are community-managed rural pre-schools serving 45 per cent of the child population. Provision of mid-morning porridge is a key incentive to attend. Save the Children and University of Malawi Chancellor College developed a nutrition and agriculture training programme for CBCCs to overcome identified challenges to CBBC food provision.